HYPNOSIS FOR SYMPTOM MANAGEMENT IN WOMEN WITH BREAST CANCER: A Pilot Study - Jensen, Mark P. (Int J Clin Exp Hypn, 2012)
Eight women who were in treatment for breast cancer (n = 4) or breast cancer survivors (n = 4), presenting with 1 or more of 4 symptoms (chronic pain, fatigue, hot flashes, and sleep difficulties), were given 4 to 5 sessions of self-hypnosis training for symptom management. Analyses revealed (a) significant pre- to posttreatment decreases in pain intensity, fatigue, and sleep problems and (b) that pain intensity continued to decrease from posttreatment to 6-month follow-up. Although there was a slight increase in fatigue severity and sleep problems from posttreatment to 6-month follow-up, the follow-up scores did not return to pretreatment levels. The findings provide initial support for using hypnosis to manage symptoms in women who are breast cancer survivors. Clinical trials evaluating hypnosis efficacy over and above other treatments are warranted.